Administration of probiotic Lactobacillus Rhamnosus GG together with celecoxib attenuates oxidative stress and modulates colonic morphology in 1,2-dimethylhydrazine-induced colon cancer in sprague dawley rats (Funding work) - LEILA KAEID SHARAF; MRIDUL SHARMA; GEETA SHUKLA (International Journal of Pharma and Bio Sciences, 2018)
Colorectal cancer arises by the genetic alterations involving variety of oncogenes and tumor suppressor genes that transform normal colonic epithelium into an invasive carcinoma. The genetic alterations appear to follow histological changes from small, pre-malignant adenomas to advanced metastatic tumors in colorectal cancer. In addition to facilitating tumor growth and survival, ROS also plays a role as an important inhibitor of cancer cell proliferation and in induction of apoptosis. Therefore, the present study was designed to assess the oxidative potential of prophylactic administration of probiotics and celecoxib (selective COX-2 inhibitor) in modulating experimental colorectal cancer vis-à-vis gut morphology. Experimentally, Sprague Dawley rats were divided into six groups and were administered with probiotics in combination with celecoxib for 18 weeks along with the inducement of tumors by 1,2-dimethylhydrazine (DMH). It was found that L.rhamnosusGG+celecoxib+DMH-treated animals showed significant decrease in malondialdehyde levels and enhanced the antioxidant levels along with mild gut histological alteration compared with L.acidophilus+celecoxib+DMH and L.acidophilus+L.rhamnosusGG+celecoxib+DMH-treated animals.